Digest of the Statutes of the State of Louisiana, Collated and Arranged under Appropriate Heads, and Embracing All the Statute Laws of the State of a General Character, Inclusive of the Acts of One Thousand Eight Hundred and Seventy, Except What are Contained in the Revised Civil Code and Code of Practice, Adopted in One Thousand Eight Hundred and Seventy Page 387, Image 399 (Vol. 1, 1870) - (:unkn) unknown (General Publisher, 1870)
If any person shall voluntarily engage in a duel with rapier or small sword, back sword, pistol or other dangerous weapon to the hazard of life, and death shall ensue, the survivor shall, upon conviction, suffer death; and all and every person aiding and abetting as second, agent or abettor, shall, on conviction, be punished as accessories before the fact in murder
--
Keywords: DUELING